Direct Conversion of Alcohols into Alkenes by Dehydrogenative Coupling with Hydrazine/Hydrazone Catalyzed by Manganese. Issue 41 (19th August 2018) - Das, Uttam Kumar; Chakraborty, Subrata; Diskin‐Posner, Yael; Milstein, David
Abstract: We have developed unprecedented methods for the direct transformation of primary alcohols to alkenes in the presence of hydrazine, and for the synthesis of mixed alkenes by the reaction of alcohols with hydrazones. The reactions are catalyzed by a manganese pincer complex and proceed in absence of added base or hydrogen acceptors, liberating dihydrogen, dinitrogen, and water as the only byproducts. The proposed mechanism, based on preparation of proposed intermediates and control experiments, suggests that the transformation occurs through metal–ligand cooperative N−H activation of a hydrazone intermediate. Abstract : In a pinch : Direct transformations of primary alcohols into alkenes by acceptorless dehydrogenative coupling of alcohols with hydrazine, and dehydrogenative coupling of alcohols with hydrazones to form mixed alkenes, are demonstrated. These reactions are catalyzed by a manganese pincer complex in absence of added base or hydrogen acceptors, and liberate dihydrogen, dinitrogen and water as the only byproducts.